Reinforcement mechanism analysis of lattice beam and prestressed anchor rod system for loess slope - Liu, Yang; Han, Dongdong; Liu, Nina; Wang, Wentao (Frontiers in Earth Science, 2023)
To enhance stability and prevent failure of soil or rock slopes, lattice beam and prestressed anchor rod (LBPAR) system can be used. In this study, a model of LBPAR system was designed with reinforcement mechanisms and a model test was constructed with a circular slip surface of a loess slope. First, interaction between the loess slope and the LBPAR system was investigated by an LBPAR system analysis model. Stability of sliding mass from the sliding bed with an arc-shaped sliding surface was then studied by an experimental model designed. Finally, internal force distribution of lattice beams in the LBPAR system was investigated by using a large-scale physical model test. The results were compared to those calculated using the reverse beam method, indicating that the LBPAR system strengthened the sliding mass in space and improved the overall stability of the loess slope. With vertical loading, the axial tensile stress of the main anchor rod increases continuously. The bending area of the anchor rod was concentrated within two meters of the sliding surface. The sliding mass was subject to vertical load pressure, lattice beams' pressure, and dead weight in the meantime and the maximum earth pressure value is near the node of the lattice beams. It is proved that such a method excels in the engineering design of loess landslides, which has promising applications in the future.